Effect of pressure on the integrity of the duct-acinar system of the pancreas. Issue 1 (January 1970) - Pirola, R. C.; Davis, A. E.
Abstract : India ink introduced into the pancreatic ducts of the cat can escape into the interstitium at pressures below the maximum secretory pressure of the pancreas. The ink appears to leave through clefts between the acinar cells.